Public Intoxication: Sobering Centers as an Alternative to Incarceration, Houston, 2010–2017 - Jarvis, Suzanne V. (Am J Public Health, 2019)
In 2010, the Houston police department admitted 20 508 publicly intoxicated individuals into its jail. To address jail overcrowding, the city created a jail diversion policy that allowed law enforcement to admit publicly intoxicated individuals into a new sobering center. By 2017, public intoxication jail admissions had decreased by 95%, freeing valuable resources. A promising public health intervention, sobering centers offer an alternative to incarceration and relieve overuse of emergency services while assisting individuals with substance use issues.